COVID-19에 대한 청폐배독탕의 연구 동향 분석 - 강보형; 최유경; 전찬용; 양승보; Kang, Bo-hyung; Choi, You-kyoung; Jeon, Chan-yong; Yang, Seung-Bo (대한한방내과학회지, 2020)
Qingfei Paidu decoction is recommended for treatment and prevention of COVID-19. It is a prescription that combines Mahaenggamseok-tang, Oryeong-san, Soshiho-tang, Saganmahwang-tang, and Kwakhyangjeonggi-san. According to several clinical reviews, symptoms of COVID-19 were improved, laboratory test indicators were improved, and the cure rate was increased. Pharmacologically, the Qingfei Paidu decoction and its composition have been reported to inhibit viral replication, alleviate immune responses, and have anti-inflammatory and antiviral effects. Severe side effects were not revealed, and this treatment is considered relatively safe. However, to validate and better understand these findings, well-designed clinical studies are needed.